2005
DOI: 10.1002/bdra.20127
|View full text |Cite
|
Sign up to set email alerts
|

Teratogen update: Lead and pregnancy

Abstract: This review focuses on the impacts of lead exposure on reproductive health and outcomes. High levels of paternal lead exposure (Ͼ40 g/dl or Ͼ25 g/dl for a period of years) appear to reduce fertility and to increase the risks of spontaneous abortion and reduced fetal growth (preterm delivery, low birth weight). Maternal blood lead levels of approximately 10 g/dl have been linked to increased risks of pregnancy hypertension, spontaneous abortion, and reduced offspring neurobehavioral development. Somewhat higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(168 citation statements)
references
References 92 publications
2
153
0
7
Order By: Relevance
“…28 Adequate calcium supplementation (1,200 mg calcium per day) 29 has been found to be an important means of limiting fetal and maternal lead toxicity especially during the second half of the pregnancy. 2 Lead-induced decreases in birth weight and length are nevertheless unlikely to be prevented. 30 During lactation, however, calcium supplementation is evidently less effective in minimizing the lead mobilization from the skeleton.…”
Section: The Role Of Calcium Supplementation During Pregnancy and Lacmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Adequate calcium supplementation (1,200 mg calcium per day) 29 has been found to be an important means of limiting fetal and maternal lead toxicity especially during the second half of the pregnancy. 2 Lead-induced decreases in birth weight and length are nevertheless unlikely to be prevented. 30 During lactation, however, calcium supplementation is evidently less effective in minimizing the lead mobilization from the skeleton.…”
Section: The Role Of Calcium Supplementation During Pregnancy and Lacmentioning
confidence: 99%
“…During pregnancy, even lower lead levels are of serious concern because of their adverse effects on the fetus, including developmental delays, low birth weight, and miscarriage. 2,3 Here, we report the case of an adult female who had last been exposed to lead 7 years earlier but now presented with symptoms and findings of acute lead poisoning which we treated with chelation therapy. In the absence of an acute lead exposure, her increased lead levels were likely due to increased mobilization and redistribution from mineralized tissues during and after a recent pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High dose occupational lead exposure, usually with BLLs greater than 40 mg/dL, may alter sperm morphology, reduce sperm count, and decrease fertility (Alexander et al, 1996;Telisman et al, 2000). At low environmental exposures, lead in women may be associated with hypertension during pregnancy, premature delivery, and spontaneous abortion (Baghurst et al, 1987;Bellinger 2005;Borja-Aburto et al, 1999).…”
Section: Urinary Lead (Creatinine Corrected)mentioning
confidence: 99%
“…Although the average blood lead level in both studies was classified as acceptable, several studies have reported adverse pregnancy outcomes occurring at these blood levels or even lower 9,16,64,65) . In addition, some of the subjects in both studies had blood lead levels greater than 20 µ g/dl, suggesting a high risk of adverse pregnancy outcomes [66][67][68] .…”
Section: Difficulties In Studying Pregnant Workersmentioning
confidence: 97%